Lost in Translation? The Terminology and Practice of Islamic Gifts in Early Modern Travel Accounts in English - Ladan Niayesh (Revue Française de Civilisation Britannique)
Symbolic performance and rhetoric of service are part and parcel of the meaning and function of gifts in any given culture. Exploring the specificity of Muslim Orient’s gift terms such as pīshkash and khil‘at, which entered the English language in the wake of trade and diplomatic interactions with the Ottomans, Safavids and Mughals in the seventeenth century, this article looks into the protocols and rituals accompanying each term, as a basis for understanding their community-building value. My case studies on the contextual uses of gift terms in travel narratives from the period include Thomas Herbert’s A Relation of Some Yeares Travaile, Begvnne Anno 1626 (1634), and the first English translation by John Phillips of Jean-Baptiste Tavernier’s Six Voyages (1677). In each case, I argue, practiced uses of terminology illustrate the visitors’ cultural and linguistic attempts, but also their failures, at understanding the host system and infiltrating it.